Fracture Network Correlation Analysis of Meta-Sediment Outcrop in Terengganu Coastline and Malay Basin - ., Liyana Rosely, Abdul Halim Abdul Latiff (2015)
B23 FRACTURE NETWORK CORRELATION ANALYSIS OF META-SEDIMENT OUTCROP IN TERENGGANU COASTLINE AND MALAY BASIN Liyana Rosely, Abdul Halim Abdul Latiff Department of Geosicences, Universiti Teknologi PETRONAS Email: liyanarosely19@gmail.com In the oil and gas industry, basins contain with fractured base ments rocks have been garnered much interest due to its fractures’ potential as a hyd rocarbon reservoir (Sircar, 2004). However, since these basements are typically me ta-sediments or igneous rock, it is generally difficult to analyze the fracture network based on seismic images, due poor seismic resolution (attenuation of higher freq uency, as highlighted in yellow in Figure 1 ) and lack of sedimentary layers with contrasting acoustic impedance. Typically, fractured basements are made of igneous a nd/or meta- sediments rocks, where the ambiguous fracture network is genera lly difficult to image, locate and interpret